Evidence-Based Predictors of the Japanese Language Proficiency Test Succes: The Role of Kanji, Grammar, Reading, and Listening Skills - Andy Moorad Oesman; Dany Buyung Yudha Prasetya; Setiyani Wardhaningtyas; Chiara Manno (Universitas Pendidikan Mandalika, 2026)
This study examined the relationship between core Japanese language competencies Kanji, Bunpou (grammar), Dokkai (reading comprehension), and Choukai (listening comprehension) and success on the Japanese Language Proficiency Test (JLPT). This quantitative, predictive correlational research involved 60 students enrolled in Universitas Negeri Semarang Japanese language program. Based on the structural equation modelling and binary logistic regression analysis, the combined effects of Kanji, Bunpou (grammar), Dokkai (reading), and Choukai (listening) on JLPT outcomes were highly significant (χ² (4) = 42.957, p < 0.001), accounting for 73.4% of the variance (Nagelkerke R2.734). The model correctly classified 95% of cases, has an 88% accuracy for failures, and has a 98% accuracy for passes, indicating its robust predictive power. All four competencies were also significantly related to JLPT performance when considered separately (all p < 0.001). However, only Kanji (p = 0.041, odds ratio ≈ 1.69) and Bunpou (p = 0.046, odds ratio ≈ 1.77) were significantly associated with JLPT performance in the simultaneous model, as the impacts of Dokkai and Choukai were not significant. These findings imply that grammar, vocabulary and Kanji are fundamental elements for Japanese language learning, with reading and listening comprehension being heavily reliant on these skills. Therefore, because mastery of both lexical and syntactic skills appears to be a prerequisite for other abilities to meaningfully influence JLPT performance, this study recommends refining the integrative linguistic threshold concept and adopting a more comprehensive ‘Foundational-First’ pedagogical framework. It further suggests structuring weekly learning cycles to prioritize intensive lexico-syntactic automatization as the essential gateway to developing higher-order reading and listening proficiency.